Integrated Islamic Learning Model for Children in Conflict with the Law - Fadila, Fadila; Danim, Sudarwan; Hadiwinarto, Hadiwinarto; Darmayana, I Wayan; Yanuarti, Eka (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to see the effect of an integrated Islamic learning model that combines general education, religious education, and skills into one Islamic learning model for children in Class II Correctional Institutions. This research employed the qualitative-descriptive approach. The subjects of this study were 21 children in conflict with the law in Class IIA Curup Correctional Institution. The data were collected using a questionnaire, interviews, and documentation with data triangulation analysis techniques. The integrated Islamic learning model combines five activities tailored to the needs of the children in conflict with the law in class IIA Curup Correctional Institution. The five activities were carried out with the help of correctional institution’s stakeholders, religious figures who taught fiqh of worship, teachers of general subjects, police officers who taught civic education, teachers who taught soft skills to make pots, and counselors who conducted individual and group counseling. As a result, All activities provided positive influence. This finding proves that the integrated Islamic learning model can support the children in conflict with the law’s development program.